Behavioral and Neuroimaging Research on Developmental Coordination Disorder (DCD): A Combined Systematic Review and Meta-Analysis of Recent Findings - Subara-Zukic, Emily; Cole, Michael H.; McGuckian, Thomas B.; Steenbergen, Bert; Green, Dido; Smits-Engelsman, Bouwien CM; Lust, Jessica M.; Abdollahipour, Reza; Domellöf, Erik; Deconinck, Frederik J. A.; Blank, Rainer; Wilson, Peter H. (Frontiers in Psychology, 2022)
Aim The neurocognitive basis of Developmental Coordination Disorder (DCD; or motor clumsiness) remains an issue of continued debate. This combined systematic review and meta-analysis provides a synthesis of recent experimental studies on the motor control, cognitive, and neural underpinnings of DCD. Methods The review included all published work conducted since September 2016 and up to April 2021. One-hundred papers with a DCD-Control comparison were included, with 1,374 effect sizes entered into a multi-level meta-analysis. Results The most profound deficits were shown in: voluntary gaze control during movement; cognitive-motor integration; practice-/context-dependent motor learning; internal modeling; more variable movement kinematics/kinetics; larger safety margins when locomoting, and atypical neural structure and function across sensori-motor and prefrontal regions. Interpretation Taken together, these results on DCD suggest fundamental deficits in visual-motor mapping and cognitive-motor integration, and abnormal maturation of motor networks, but also areas of pragmatic compensation for motor control deficits. Implications for current theory, future research, and evidence-based practice are discussed. Systematic Review Registration PROSPERO, identifier: CRD42020185444.